Chemical components of essential oils of muña minthostachys mollis (kunth.) griseb. in Huánuco - Maquera Lupaca, David (2009)
The research work about the extraction of the essential oils of muña Minthostachys mollis, it was carried out in the laboratory of Chemistry of the Hermilio Valdizan National University of Huánuco, the leaves sample were taken from the localities of Mitocucho (3050 masl) of the district of Kichki and province of Huanuco and Tambillo (2500 masl) district and province of Pachitea. For the extraction of the essential oils, it was used the method of distillation by steam dragging. The determination of the chemical components of the essential oils was carried out in two Hollanders laboratories: International Quest and Givaudan, for the method of d e cromatografía of gases / spectrometries of masses (CG/MS). Of the analyses studied in the essential oils, the main component of the essential oils is the pulegone followed in concentration by the menthone.